Inhibition of Lipopolysaccharide- and Lipoprotein-Induced Inflammation by Antitoxin Peptide Pep19-2.5 - Heinbockel, Lena; Weindl, Günther; Martinez-de-Tejada, Guillermo; Correa, Wilmar; Sanchez-Gomez, Susana; Bárcena-Varela, Sergio; Goldmann, Torsten; Garidel, Patrick; Gutsmann, Thomas; Brandenburg, Klaus (Frontiers in Immunology, 2018)
The most potent cell wall-derived inflammatory toxins (‘pathogenicity factors’) of Gram-negative and –positive bacteria are lipopolysaccharides (LPS, endotoxins) and lipoproteins (LP), respectively. Despite the fact that the former signals via Toll-like receptor 4 (TLR4) and the latter via TLR2, the physico-chemistry of these compounds exhibits considerable similarity, an amphiphilic molecule with a polar and charged backbone and a lipid moiety. While the exterior portion of the LPS (i.e. the O-chain) represents the serologically relevant structure, the inner part, the lipid A, is responsible for one of the strongest inflammatory activities known. In the last years, we have demonstrated that antimicrobial peptides from the Pep19-2.5 family, which were designed to bind to LPS and LP, act as anti-inflammatory agents against sepsis and endotoxic shock caused by severe bacterial infections. We also showed that this anti-inflammatory activity requires specific interactions of the peptides with LPS and LP leading to exothermic reactions with saturation characteristics in calorimetry assays. Parallel to this, peptide-mediated neutralization of LPS and LP involves changes in various physical parameters, including both the gel to liquid crystalline phase transition of the acyl chains and the three-dimensional aggregate structures of the toxins. Furthermore, the effectivity of neutralization of pathogenicity factors by peptides was demonstrated in several in vivo models together with the finding that a peptide based therapy sensitizes bacteria (also antimicrobial resistant) to antibiotics. Finally, a significant step in the understanding of the broad anti-inflammatory function of Pep19-2.5 was the demonstration that this compound is able to block the intracellular endotoxin signaling cascade.